2000
DOI: 10.1159/000008767
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Allopurinol in Hepatic Ischemia and Reperfusion: Experimental Study in Rats

Abstract: Background/Aims: Some studies have shown that postischemic hepatic dysfunction is mainly due to oxygen free radicals that are generated by xanthine oxidase. The present study was undertaken to determine the effect of allopurinol, an inhibitor of xanthine oxidase, on oxidative stress, liver injury and histologic alterations induced by hepatic ischemia-reperfusion in rats. Methods: One hundred and sixty Wistar rats were used and divided into three groups. Group 1: sham operation; group 2: 50 min of ischemia foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Allopurinol was administered to rats i.p. (50 mg͞kg), 24 and 5 h before the injection of sodium formate and POBN (16). AT was given to rats (1 g͞kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Allopurinol was administered to rats i.p. (50 mg͞kg), 24 and 5 h before the injection of sodium formate and POBN (16). AT was given to rats (1 g͞kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…There are a few studies that have shown allopurinol has no effect on transaminases [5,44] and that LDH [42,45] increases. In most cases, if the attenuation in transaminase increases was not seen immediately, it occurred at least 5 h after reperfusion had elapsed [10,37,41,42]. However when the period was extended to 24 h, no effect was observed by Metzger et al [5].…”
Section: Allopurinol Protection In Liver Ir As Measured By Markers Ofmentioning
confidence: 97%
“…Rhoden et al [41] 2001 Rat Liver IR ALLO pretreatment protects against mitochondrial injury, which prevents mitochondrial oxidant stress and lipid peroxidation and preservation of hepatic energy metabolism.…”
Section: Allopurinol Protection In Liver Ir Injury As Measured By Hismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on hepatic I/R models have shown greater free radical generation with continuous clamping techniques [30]followed by rapid exhaustion of naturally occurring endogenous anti-oxidants during the reperfusion periods. Here, a range of administered free radical scavengers and inhibitors have been shown experimentally to attenuate free radical generation including superoxide dismutase, allopurinol, N-acetylcysteine and α-tocopherol [31, 32, 33]. DMSO was utilized in this study partly because of its Na + -K + - ATPase inhibiting properties, since it was hoped that this would affect the reduction reported in intracellular ATP frequently observed during experimental ischaemia [34].…”
Section: Discussionmentioning
confidence: 99%